1995
DOI: 10.1007/bf00801622
|View full text |Cite
|
Sign up to set email alerts
|

Efficient one-step direct labelling of recombinant antibodies with technetium-99m

Abstract: High-affinity bacterially expressed antibody fragments can nowadays be cloned from established hybridomas or, more conveniently, isolated directly from antibody libraries displayed on filamentous phage. Such antibodies can be tagged with C-terminal peptide tags containing one cysteine residue, which represents a convenient functionalisation site for a number of applications, including technetium-99m labelling. Here we describe a simple one-step method for 99mTc labelling of cysteine-tagged recombinant antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Labelling of scFv with Technetium-99m at single specific sites remote from the binding domains has been successful for imaging applications (Liberatore et al, 1995;Verhaar et al, 1996) but is less sensitive than iodine. However, one disadvantage of iodination is that it modifies tyrosine residues including those in the antigen binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Labelling of scFv with Technetium-99m at single specific sites remote from the binding domains has been successful for imaging applications (Liberatore et al, 1995;Verhaar et al, 1996) but is less sensitive than iodine. However, one disadvantage of iodination is that it modifies tyrosine residues including those in the antigen binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The Cys thiol group, along with 3 amides in the peptide backbone, creates a site-specific N 3 S chelator for labeling with 99m Tc, resulting in a controlled, homogeneous product. This approach has been applied for the labeling of single-chain Fv fragments (23)(24)(25). We previously evaluated the labeling of Affibody molecules with CGG and CGGG sequences incorporated at the N terminus of Affibody molecule Z HER2:342 (26).…”
mentioning
confidence: 99%
“…Mercaptoacetyl‐containing SN 3 ‐chelators can be site‐specifically introduced into peptides by employing chemical synthesis . When using recombinantly produced proteins, a site‐specific chelator can be introduced by the engineering of a unique cysteine into the peptide sequence . Experience with Affibody molecules carrying different peptide‐based chelators labeled with 99m Tc has furthermore shown that the residualizing properties of 99m Tc are influenced by the side‐chains of the amino acids participating in the coordination of 99m Tc, as further described in Section .…”
Section: Radionuclides For Labeling Of Peptides and Proteins For Molementioning
confidence: 99%